Effective Amelioration of Liver Fibrosis Through Lentiviral Vector Carrying Toxoplasma gondii gra15II in Murine Model - Liu, Lei; Jin, Mengmeng; Tao, Qing; Yu, Li; Du, Jian; Wang, Cong; Luo, Qingli; Xing, Tian; Xu, Yuanhong; Shen, Jilong; Chu, Deyong (Frontiers in Immunology, 2018)
Our previous investigations indicated that in vitro polarization of mouse macrophages by Toxoplasma gondii type II strain dense granule protein 15 (GRA15II), one of the genotype-associated effectors of T. gondii, induced the phenotypes of classically activated macrophage (M1). Transfusion of the cells to mice may effectively alleviated hepatic fibrosis caused by schistosomiasis. The purpose of the study was to identify whether liver macrophages can be in vivo driven to M1 macrophages by lentiviral vector (LV) carrying GRA15II gene (LV-gra15II) and to explore the potential mechanism by which the LV-gra15II-activated liver macrophage (LV-gra15II-M) ameliorates the hepatic fibrosis in schistosomiasis. The mice were treated with LV-gra15II by hydrodynamic injection via the tail vein followed by challenge of Schistosoma japonicum (S. japonicum). Our experiments showed that LV-gra15II was successfully delivered to liver macrophages and GRA15II was persistently expressed in the macrophages of mice for at least 2 months. Furthermore, the LV-gra15II infected macrophages were polarized to M1 macrophages in vivo. Consequently, mice with schistosomiasis receiving LV-gra15II injection displayed a remarkable amelioration of liver granuloma formation and collagen deposition in association with downregulated expression of transforming growth factor-beta1, arginase 1 (Arg-1), α-smooth muscle actin, and an increased expression of matrix metalloproteinase 13 (MMP13). Simultaneously, no negative effects of liver function and vitality of mice were noted. The in vitro experiments indicated that the C-C motif chemokine ligand 2 and nitric oxide level were elevated in LV-gra15II-M cultural supernatants; hepatocyte growth factor expression was enhanced in LV-gra15II-M. In addition, LV-gra15II-M not only secreted MMP13, which greatly degraded type I collagen, but also induced murine hepatic stellate cell (HSC) line (JS1) apoptosis in the co-culture system. Taken together, we identified for the first time that LV-gra15II may in vivo drive liver macrophages to M1 macrophage phenotypes, which helps for alteration of the liver fibrotic microenvironment with collagen dissolution, HSC deactivation, apoptosis and hepatocyte protection. Our study gives an insight into the use of gene delivery with parasite-derived immunomodulatory factor as a potential immune cell activating agent to re-equilibrate the other pathogen-induced immune response in some chronic diseases.